Thailand : Financial Sector Assessment Program-Detailed Assessment of Observance-Basel Core Principles For Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2019)
This Detailed Assessment of Observance on the Basel Core Principles (BCP) for effective banking supervision on Thailand highlights that there have been significant enhancements to the legal framework and the supervisory process since the last BCP review, resulting in high compliance. The commercial banking sector appears to be sound and stable with a diversified lending profile and a steady source of funding. The involvement of other ministerial authorities in Specialized Financial Institutions supervision may affect standard-setting processes and the mindset of key decision makers for commercial banks when trying to level regulatory standards. The supervisory framework and practices provide the foundation for the continued development of risk-based supervision. Notifications and examination manuals increasingly focus on analysis of qualitative factors such as governance, risk management and risk appetite statements to determine the bank's composite rating. The report recommends that efficiency of enforcement actions would be increased by aligning Financial Institutions Business Act requirements and Bank of Thailand internal practices.